Ukraine invasion - mass blocks (Russia) - Voidly (2022)
CRITICAL severity censorship detected in Russia. Confidence: 95%. Data sourced from OONI.
Censorship Incident ID: RU-2022-0001
Keywords: censorship; RU; censorship; critical